Malaria and anaemia in pregnant and non-pregnant women of child-bearing age: a cross-sectional study - Romday, Rakesh; Gupta, Ajay Kumar; Chilloria, Pawan; Sharma, Satendra; Bhambani, Pawan (International Journal of Advances in Medicine, 2017)
Background: Malaria infection during pregnancy is a major public health problem globally. Anaemia is often an adverse outcome of severe parasitic infections during pregnancy in developing countries. Pregnant are more susceptible to Plasmodium falciparum infections than non-pregnant women of child-bearing age. The objective of this study was to comparatively investigate malaria and anaemia in pregnant and non- pregnant women of child-bearing age. Methods: A cross-sectional comparative study, in which 380 pregnant women and 380 non-pregnant women were screened for the study. The study was conducted at the Index Medical College Hospital and Research Centre, Indore, Madhya Pradesh, India. Participants’ demographic data were collected via the administration of questionnaires. In addition, their blood samples were analysed for haemoglobin level and Malaria parasites, while stool samples from the pregnant women were examined for intestinal parasites. Results: The study revealed that pregnant women have higher malaria parasitaemia (12.6%) and anaemia (62.6%). The species of Plasmodium isolated from the pregnant women were P. falciparum (85.4%), P. malariae (4.2%) and P. ovale (10.4%). Malaria parasitaemia was higher in the primigravidae (14%). However multi-gravidae recorded the highest anaemia prevalence (67.1%). Age of pregnant women was a factor affecting malaria parasitaemia with a significant P-value and (P value = 0.0041). Conclusions: Pregnant women were more susceptible to malaria and anaemia than non-pregnant women of child-bearing age. Most of the pregnant women reported at antenatal clinic during the second trimester. Primigravidae however recorded the highest malaria parasitaemia. The main species of Plasmodium observed in the blood samples was falciparum.